To trust or distrust?: Unpacking ethnic minority immigrants’ trust in police - Pass, Michael D. (The British journal of criminology, 2020)
Studies find that immigrants can be less trusting of police than non-immigrants, with immigrants’ views deteriorating as their length of residence in a host country increases. However, existing research has failed to consider different dimensions of trust. This study applies different trust measures (single-item and multi-item measures) to examine whether trust in police varies by immigrant status and length of residence. Using survey data from 1,367 first- and second-generation ethnic minority immigrants in Australia, we find that the effect of immigrant status and length of residence on trust varies depending on how trust in police is measured. The theoretical and policy implications of these findings are discussed.